1991
DOI: 10.1093/ndt/6.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Metabolism in Early Chronic Renal Failure: Implications for the Pathogenesis of Hyperparathyroidism

Abstract: Studies in the past showed elevated immunoreactive parathyroid hormone (PTH) serum values in early renal failure, but the assays used in these studies could not discriminate between bioinactive fragments of the PTH peptide and biologically active hormone. The availability of a sensitive PTH assay, which quantitates intact hormone, now allows the analysis of biologically active PTH in renal failure. To characterise more precisely the point of onset of hyperparathyroidism in the course of chronic renal failure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
1
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 0 publications
7
76
1
7
Order By: Relevance
“…The conversion of calcidiol (25(OH)D 3 ) to the metabolically most active form of vitamin D, the D-hormone (calcitriol/1.25(OH) 2 D 3 ), is highly dependent on the creatinine clearance [18,19]. It is hypothesized that below a creatinine clearance of 60 ml/min [20] or 50 ml/ min [21], the renal conversion of 25(OH)D 3 to 1.25(OH) 2 D 3 becomes insufficient [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of calcidiol (25(OH)D 3 ) to the metabolically most active form of vitamin D, the D-hormone (calcitriol/1.25(OH) 2 D 3 ), is highly dependent on the creatinine clearance [18,19]. It is hypothesized that below a creatinine clearance of 60 ml/min [20] or 50 ml/ min [21], the renal conversion of 25(OH)D 3 to 1.25(OH) 2 D 3 becomes insufficient [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, this factor should not be the only one, since many patients who did not have nephrotic proteinuria also presented with vitamin D deficiency. 24 However, it is important to observe that the high frequency of vitamin D deficiency in our sample of patients with CKD (73.6%) is not different from that recently demonstrated in healthy people living in São Paulo, in which 77.4% of the people presented serum levels of 25(OH)D < 30 ng/mL. 13 The consequences of vitamin D deficiency in patients with CKD are not established yet.…”
Section: Discussionmentioning
confidence: 61%
“…24,25 Likewise, it is a known fact that the presence of nephrotic proteinuria is associated with vitamin D deficiency, possibly due to the urinary loss of vitamin D bound to its plasma carrier protein. 26 As to the patients analyzed in this study, those who had the nephrotic syndrome presented serum levels of 25(OH)D ≤ 30 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…31 The conversion of calcidol (25-hydroxyvitamin D) to the most active metabolic form of vitamin D, calcitriol (1,25-dihydroxyvitamin D), is highly dependent on the renal function. 32,33 Thus, one possible explanation of the higher incidence of falls in the older group may be attributable to an agerelated increase in the prevalence of renal dysfunction, although a secondary data analysis of women participating in the FIT demonstrated that ALN treatment increased BMD and decreased the relative risk, but not the absolute risk, of clinical fractures to a similar degree among women with and without reduced renal function. 34 Impairment of muscle strength and muscle power of the lower extremities, balance/postural control, and walking ability has been recognized as important risk factors for falls.…”
Section: Discussionmentioning
confidence: 99%